MYC dephosphorylation by the PP1/PNUTS phosphatase complex regulates chromatin binding and protein stability - Dharmendra Dingar (Nature Portfolio, 2018)
Deregulated MYC activity is oncogenic and is deregulated in a large fraction of human cancers. Here the authors find that protein phosphatase 1 and its regulatory subunit PNUTS controls MYC stability and its interaction with chromatin.